1996
DOI: 10.1111/j.1432-1033.1996.00738.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of the Metabolic Pools of Sphingomyelin and Phosphatidylcholine Sensitive to Tumor Necrosis Factor

Abstract: The metabolism and localization of the pools of sphingomyelin and phosphatidylcholine (PtdCho) which are hydrolyzed upon activation of the sphingomyelin signal transduction pathway were studied in human skin fibroblasts treated with tumor necrosis factor a (TNF-a). In a first series of experiments, cellular phospholipids were labeled with [3H]choline under conditions that inhibit the vesicular traffic to the plasma membrane. Thus, in human fibroblasts metabolically labeled in the presence of brefeldin A, monen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
59
1
1

Year Published

1996
1996
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(69 citation statements)
references
References 69 publications
7
59
1
1
Order By: Relevance
“…Treatment of Jurkat and U937 cells with a combination of monensin and EDTA, in the absence of TNF and anti-Fas, caused a greater increase in the ceramide to sphingomyelin ratio (47 and 66%, respectively). This fact was probably due to the intracellular accumulation of ceramide by monensin blockade of its transport to the plasma membrane (Kallen et al, 1993;Andrieu et al, 1996). This increase in the cell ceramide content was not associated, however, with any observable cytotoxicity during the experimental period, in spite of being greater than that induced by anti-Fas or TNF (Figure 2).…”
Section: Effect Of Sphingomyelinase Inhibitors On Ceramide Generationmentioning
confidence: 87%
See 2 more Smart Citations
“…Treatment of Jurkat and U937 cells with a combination of monensin and EDTA, in the absence of TNF and anti-Fas, caused a greater increase in the ceramide to sphingomyelin ratio (47 and 66%, respectively). This fact was probably due to the intracellular accumulation of ceramide by monensin blockade of its transport to the plasma membrane (Kallen et al, 1993;Andrieu et al, 1996). This increase in the cell ceramide content was not associated, however, with any observable cytotoxicity during the experimental period, in spite of being greater than that induced by anti-Fas or TNF (Figure 2).…”
Section: Effect Of Sphingomyelinase Inhibitors On Ceramide Generationmentioning
confidence: 87%
“…The effect of several drugs, which interfere with ceramide metabolism, on TNF and Fasmediated apoptosis was also evaluated. These were FB 1 (25 ± 50 mM), an inhibitor of ceramide synthase (Jaffre  zou et al, 1996), the lysosomotropic agents chloroquine (10 mM), ammonium chloride (8 mM) and monensin (1 ± 10 mg/ml), all of which inhibit acid sphingomyelinase activity (Wiegmann et al, 1994;Tepper et al, 1995;Andrieu et al, 1996), and EDTA (1 mM), a Ca 2+ -and Mg 2+ -chelator which inhibits the activity of neutral, Mg 2+ -dependent, sphingomyelinase (Futerman et al, 1990). Chloroquine was dissolved in RPMI medium, EDTA and FB 1 in PBS and monensin in ethanol.…”
Section: Cell Culture and Analysis Of Cell Deathmentioning
confidence: 99%
See 1 more Smart Citation
“…4,46,47 Interestingly, the location of the sphingomyelin pool hydrolyzed by TNF-a is controversial. Several investigators have proposed that the TNF-asensitive pool resides in the external leaflet of the plasma membrane.…”
Section: Discussionmentioning
confidence: 99%
“…48 Others proposed that the sphingomyelin pool hydrolyzed by TNF-a is localized in the endolysosomal compartments 4 or the inner leaflet of the plasma membrane. 47,49 One could argue that exogenous ceramide kills cells with different kinetics, because of its differential accumulation in subcellular compartments that are different from those generated by TNF-a. Studies with synthetic fluorescent ceramide analogs have shown ceramide to accumulate in the Golgi apparatus and sequentially in other membrane compartments 39 suggesting that cellular membranes are saturated quickly in the presence of exogenous ceramide.…”
Section: Discussionmentioning
confidence: 99%